Effect of health literacy program on improving elderly women’s awareness regarding atrophic vaginitis - Mohammed, Aya Hamada Mohammed; Abd Allah, Eman Shokry; Elbadwy , Reda Elsaid (Journal of Neonatal Surgery, 2024)
Background: As the number of elderly persons in our country increases, atrophic vaginitis affects 10 to 40% of postmenopausal women worldwide. Promotion of health literacy level is one of the main non-pharmaceutical measures proposed to older adults. The aim of the study was to evaluate the effect of effect of health literacy program on improving elderly women’s awareness regarding atrophic vaginitis. Subjects and Methods: Research design: A quasi-experimental design was adopted to carry out this study. Setting: The study was conducted at Geriatric Social club at Zagazig city. Subjects: Purposive sample of 70 elderly women who fulfilled the study inclusion criteria. Tools for data collection: Tool I: A structured interview questionnaire was used for data collection. It was composed of three parts. (Part I) elderly women demographic characteristics, (Part II) medical and obstetric history and (Part III) Risk factors of atrophic vaginitis. Tool II: Awareness of elderly women regarding atrophic vaginitis. Results: Out of the 70 elderly women, only 18.6% of the studied elderly women had satisfactory total knowledge regarding atrophic vaginitis pre the program, which improved to 65.7% post program. Additionally, there was a highly statistically significant positive correlations between the studied elderly women’ knowledge, self- care practice pre and post program at (p < 0.01), and there was a highly statistically significant difference between pre & posttest program as regarding health literacy awareness about atrophic vaginitis for elderly women. Conclusion: The health literacy program produced substantial, clinically meaningful improvements in knowledge among elderly women with atrophic vaginitis, translating into greater symptom awareness. Recommendations: Integrating culturally tailored education into geriatric and primary care pathways which, encourage healthy and positive awareness about atrophic vaginitis in women in early age rather than teaching them when grown up.